Finite element modeling of SAW resonator in CMOS technology for single and double interdigitated electrode (IDT) structure - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Hashim, Uda (2013)
The performance of surface acoustic wave resonator in CMOS technology for single and double electrode (IDT) structure is presented. Interdigitated electrodes (IDT) structure in surface acoustic wave (SAW) resonator is the most crucial component for excitation of SAW devices. Possible configurations for the IDT are single electrode and double electrode. The performance of the resonator for single and double electrode is compared at a frequency range of 0.5 GHz to 1 GHz. 2D Finite element modeling of the CMOS SAW resonator was simulated using COMSOL Multiphysics® for three step analysis eigen frequency, frequency domain and time domain analysis. The structure and dimension of the device is based on 0.18 μm RF CMOS process where the pattern of IDT is fabricated using standard CMOS fabrication process. The simulated results shows high quality factor in the order of thousands for double electrode CMOS SAW resonator compared to single electrode CMOS SAW resonator.